PENINGKATAN SIKAP PEDULI SOSIAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MELALUI MODEL DILEMA MORAL PADA SISWA KELAS V SDN MENTENG ATAS 14 - Elisabet Simbolon; Nina Nurhasanah; Waluyo Hadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to improve students' social care attitudes through the Moral Dilemma learning model among fifth-grade students at SDN Menteng Atas 14. This classroom action research followed the Kemmis and McTaggart model, conducted over two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subjects of this study were 24 students of class V-A at SDN Menteng Atas 14. The research was conducted during the even semester of the 2025/2026 academic year. Research data were obtained through questionnaires, observations, field notes, and documentation. The results showed a significant improvement in students' social care attitudes. In the pre-research stage, only 8 students reached the mastery criteria with a percentage of 33.3%. In Cycle I, the number of successful students increased to 16, reaching a percentage of 66.6%. In Cycle II, a further increase occurred with 21 students reaching the mastery criteria, resulting in a percentage of 87.5%. Furthermore, improvements were also observed in classroom learning activities. Teacher activity in Cycle I reached 83.3% and increased to 100% in Cycle II. Student activity in Cycle I reached 80% and increased to 96.6% in Cycle II. Based on the results of this study, it can be concluded that the implementation of the Moral Dilemma learning model can effectively improve the social care attitudes of fifth-grade students at SDN Menteng Atas 14.